Comparison of intra-articular lidocaine versus intravenous sedative and analgesic for reduction of anterior shoulder dislocation in terms of mean pain reduction using vas score - Rahman Rasool Akhtar; Muhammad Umair Qammar; Riaz Ahmed; Adnan Arif; Armaghana Qamar Khan; Maria Liaquat (Journal of Rawalpindi Medical College)
INTRODUCTION: